2004
DOI: 10.1021/es030107x
|View full text |Cite
|
Sign up to set email alerts
|

Polybromodiphenyl Ether Flame Retardants in Fish from Lakes in European High Mountains and Greenland

Abstract: Individual polybromodiphenyl ethers (PBDEs) were investigated in liver and muscle tissue of trout from 11 high mountain lakes in Europe and one in Greenland. Trouts in these lakes [brown trout (Salmo trutta), brook trout (Salvelinus fontinalis) and arctic char (Salvelinus alpinus)] are important sentinel species because they are located in the top of the food chain and pollution can only reach these ecosystems by atmospheric transport. The major PBDE congeners were BDE 47 and BDE 99, followed by BDE 100, BDE 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
43
2
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 33 publications
17
43
2
2
Order By: Relevance
“…3). The predominance of BDE47 has been reported in previous assessments on PBDEs in aquatic organisms [32,33]. Brominated diphenyl ether-154's predominance over BDE153 and that of BDE100 over BDE99 in fish have also been reported in previous studies [19,34].…”
Section: Pbde and Non-pbde Frssupporting
confidence: 74%
“…3). The predominance of BDE47 has been reported in previous assessments on PBDEs in aquatic organisms [32,33]. Brominated diphenyl ether-154's predominance over BDE153 and that of BDE100 over BDE99 in fish have also been reported in previous studies [19,34].…”
Section: Pbde and Non-pbde Frssupporting
confidence: 74%
“…BDE-99 was constant in muscle and adipose tissue, slightly increased in liver and gills, and signifi cantly decreased in the kidneys with fi sh size growth. Vives et al (2004) found that the concentrations of most PBDEs in liver were correlated with fi sh age, this cannot apply to muscles. There is also evidence that the age of fi sh (Weijs et al 2009 concentrations and size or length suggesting that the fl uxes of PBDEs are still not constant (Vives et al 2004).…”
Section: Pbdes Distribution In Organs and Tissues Of Fi Shmentioning
confidence: 92%
“…Vives et al (2004) found that the concentrations of most PBDEs in liver were correlated with fi sh age, this cannot apply to muscles. There is also evidence that the age of fi sh (Weijs et al 2009 concentrations and size or length suggesting that the fl uxes of PBDEs are still not constant (Vives et al 2004). This research showed that it should be treated differently to each congener, especially those typical ones that have higher pollution levels in environmental matrix when the relationship between distribution pattern in tissues and fi sh size was analyzed.…”
Section: Pbdes Distribution In Organs and Tissues Of Fi Shmentioning
confidence: 92%
“…Due to their persistence and lipophilic properties, PBDEs can accumulate in the fatty tissues of various organisms [2]. Studies have shown that PBDEs are present in the liver and/ or muscle tissues of many fish species [3][4][5][6]. Detectable levels of PBDEs have also been reported in whole-fish homogenates of various types of marine and freshwater fish [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%